Waste characterization and water quality assessment along the Tarlac River irrigation system - Padre, Joben Ryan A.; Macasieb, Reygie Q.; Diola, Ma. Brida Lea D. (Quezon City College of Engineering, University of the Philippines Diliman, 2017)
Tarlac Province is one of the top producers of rice in the country, and the Tarlac River Irrigation System (TARRIS) provides water for agriculture to multiple municipalities in the province. Due to continuous development and urbanization, the water along the TARRIS canals is potentially polluted because of the discharge of used water and the accumulation of solid wastes. The main purpose of this research is to assess the water quality along the irrigation system. The study also aims to characterize the solid waste dumped and to analyze the effluents discharged along the TARRIS main canal. The sources of pollution were noted and mapped. Samples were collected for solid waste characterization and for both in-situ and laboratory water quality analyses. The solid waste characterization showed that plastics, diapers, and rubber materials were the main components of solid wastes dumped along the TARRIS, and that the effluents were unsatisfactory in terms of total dissolved solids and dissolved oxygen. It was found that the water quality along the canal was satisfactory in terms of pH and TDS but failed to meet standards for temperature and DO. Chemical oxygen demand was also significantly high for the water along the canal especially in the middle segment of the study area, and a corresponding percent reduction in yield was calculated for each COD value. Nitrates and Phosphates were also analyzed despite potential preservation errors.Additionally, a perception survey was carried out to get the viewpoints of residents, farmers, and barangay captains. Government offices were also inquired to obtain information on the study area and to get insights from an administrative point of view.
Thesis (Bachelor of Science in Civil Engineering)--University of the Philippines Diliman
Keywords: Water quality -- Measurement; Waste disposal in rivers, lakes, etc. -- Philippines -- Tarlac; Tarlac River Irrigation System (TARRIS).